2019
DOI: 10.1111/iju.13950
|View full text |Cite
|
Sign up to set email alerts
|

Helper T‐cell signaling and inflammatory pathway lead to formation of calcium phosphate but not calcium oxalate stones on Randall's plaques

Abstract: Objectives To elucidate the difference in the lithogenesis of calcium oxalate and calcium phosphate stones. Methods Renal papillary tissues were obtained from 23 idiopathic calcium oxalate and seven calcium phosphate stone patients who had undergone endoscopic lithotripsy. Samples were individually collected from two different regions in each patient: the papillary mucosa containing Randall's plaque and mucosa not containing Randall's plaque. A microarray analysis was carried out on those tissues to compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This study did not reveal a significant difference in the cortical or medullary T lymphocyte distribution of nonstone formers compared with stone formers. Upregulation of the T helper signaling pathway within the Randall’s plaque-containing papilla of calcium phosphate stone formers has been reported (31), and other studies suggest the possibility that T cell stimulation is followed by macrophage activation (32). It has also been reported that T cell migration was stimulated by treatment with exosomes derived from calcium oxalate–treated macrophages (29).…”
Section: Discussionmentioning
confidence: 99%
“…This study did not reveal a significant difference in the cortical or medullary T lymphocyte distribution of nonstone formers compared with stone formers. Upregulation of the T helper signaling pathway within the Randall’s plaque-containing papilla of calcium phosphate stone formers has been reported (31), and other studies suggest the possibility that T cell stimulation is followed by macrophage activation (32). It has also been reported that T cell migration was stimulated by treatment with exosomes derived from calcium oxalate–treated macrophages (29).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we did not assess bone resorptive inflammatory cytokines, such as IL-1β, IL-6, and TNF-α. We have reported that these cytokines can trigger inflammatory macrophage activation and induce renal stone formation in mice and humans (24)(25)(26)(27)(28)(29) . In addition, IL-1β and TNF-α are increased during spaceflight, with a trend for increased IL-6 (30).…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that these cytokines can trigger inflammatory macrophage activation and induce renal stone formation in mice and humans. ( 24 , 25 , 26 , 27 , 28 , 29 ) In addition, IL‐1β and TNF‐α are increased during spaceflight, with a trend for increased IL‐6. ( 30 ) Further studies are needed to assess changes in these blood and urinary cytokines as risk factors for renal stone formation during spaceflight.…”
Section: Discussionmentioning
confidence: 99%
“…In the renal papillae containing the Randall’s plaques (thought to be the starting point of stone formation), the helper T-cell signaling pathway protein is upregulated. Thus, helper T-cell immune responses and associated inflammatory processes appear to lead to the formation of calcium phosphate stones on Randall’s plaques ( Taguchi et al, 2019 ).…”
Section: Osteopontin Induces the Production Of Inflammatory Immune Ce...mentioning
confidence: 99%